Theoretical Simulation of Thermal Deformations in Concrete Beams Reinforced with Two Overlapped FRP Bars in Cold Regions - Zaidi, Ali; Bellakehal, Hizia; Masmoudi, Radhouane; Terbagou, Oumelkhir; Nia, Naima (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
The thermal incompatibility in transverse direction between concrete and fiber reinforced polymer (FRP) bars may cause tensile circumferential cracks within concrete under low temperatures, and consequently, the failure of concrete cover. This paper presents a theoretical study to investigate the transverse thermal deformation of concrete beams reinforced with two overlapped FRP bars in cold regions where the climate temperature may drop to -40°C.. Numerical and analytical models are developed to predict the transverse thermal strains at the FRP bar/concrete interface of the concrete cover zone and the bars interaction zone and also at the external surface of concrete cover for overlapped glass FRP (GFRP) bars reinforced concrete beams under low temperature variations, having a ratio of concrete cover thickness to FRP bar diameter varied from 1.0 to 3.2. Comparisons between the results predicted from non-linear finite element model and those obtained from the analytical model in terms of transverse thermal strains are presented.